Analisis Pemberian Pembiayan Mikro di Bank Syariah - zinniah al anhar (AGHNIYA : Jurnal Ekonomi Islam, 2019)
ABSTRACT Financing is one of the main tasks of the bank, namely the provision of funds provision facilities to meet the needs of the parties which constitute a unit deficit. In providing financing, Islamic banks usually provide financing by way of profit sharing or buying and selling. Where the profit sharing is called mudharabah and sale and purchase is called murabahah. Bank Syariah Mandiri carries out micro-business financing using murabahah contracts, while murabahah contracts are sale and purchase contracts. This research is a descriptive study, namely research that seeks to explain the problem solving, by presenting, analyzing and interpreting the results of research. The data collection technique carried out was through interviews. Based on the results of the research of the author, the PT. Bank Syariah Mandiri Medan Aksara Branch Office in providing micro business financing to independent Islamic banks, submitting applications, carrying guarantees, carrying identity cards, purchased goods must be halal, calculating the acquisition of funds purchased, and protecting in fees provided by the bank. This of course is in accordance with the existing DSN fatwa, regarding the murabahah contract.Keywords: Financing, Micro Business, Murabahah Agreement.